Transcriptomic changes in donor soybean, dodder bridge, and the connected recipient soybean induced by cadmium addition - Pan, Hangkai; Zhou, Li; Li, Junmin (Frontiers in Plant Science, 2025)
BackgroundCuscuta spp. (dodders) are parasitic plants that belong to the Convolvulaceae family. In nature, dodder often forms a bridge-like connection between two or more host plants like, which is known as a dodder bridge. Cadmium (Cd2+) is an important heavy metal ion that affects plant growth. However, it remains unclear whether Cd2+ treatment can directly or indirectly induce transcriptomic changes in plants through dodder bridge.ResultsIn this study, a pot experiment was conducted to investigate the effects of Cd2+ treatment on donor plant and neighboring recipient plant connected by dodder bridge. Transcriptome analysis revealed that Cd2+ treatment significantly affected the expression of genes involved in the ‘Plant-pathogen interaction’, ‘phenylpropanoid biosynthesis’, and ‘isoflavonoid biosynthesis’ pathways in both donor and recipient plants at 2, 12, 24, and 48 h. Cd2+ indirectly induced changes in the dodder bridge, which included processes related to oxidation-reduction (‘oxidation-reduction process’, ‘oxidoreductase activity’, and ‘regulation of transcription’) and Ca2+ signaling pathways (‘Plant-pathogen interaction’, ‘MAPK signaling pathway’, ‘AMPK signaling pathway’, ‘mTOR signaling pathway’). Additionally, mRNA transfer was observed from soybean to dodder. mRNA, Ca2+ and ROS might play crucial roles in the signal transduction process induced by Cd2+ stress.ConclusionCd2+ treatment could directly and indirectly induce transcriptomic changes in the donor plant and neighboring recipient plant connected by dodder bridge. These results contribute to a better understanding of how plants connected by dodder bridges respond to environmental stresses.